MENENTUKAN KELAYAKAN USAHA DENGAN METODE DENGAN METODE NPV DAN IRR BAGI SISWA SMK MUHAMMADIYAH JEMBER - Karim, M. Ainul; S, Raja Eko Dwi; A, Oky Yudi; Yahya, Helmi; Bagus, Wahyu; Firmansyah, Muhammad; Azizah, Nur Jannah; L, Adinda Fitriyah; Aini, Qurrotul; Gunasti, Amri (Jurnal Abdi Insani, 2024)
Community service by students is an effort by students to assist and provide services to the community with the aim of improving and empowering the community through the application of applications, designs, technology, or positive social change. The problem faced by high school students, especially vocational schools, is the lack of provision about making a business, especially determining the feasibility of a business. To help this, a service was held by students on financial feasibility material using the NVP and IRR methods. So that students of SMK Muhammadiyah Jember have a view if they want to start a business what must be carefully prepared so that the decisions taken are not wrong steps. Starting from preparation to implementation and report writing was carried out in May 2024. The type of activity held was socialization. The activity was carried out as scheduled and attended by around 13 participants. The socialization went smoothly and was attended by 11th grade students of SMK Muhammadiyah Jember. From the socialization activities that have been carried out, it can be concluded that this activity can increase the knowledge of 11th grade students of SMK Muhammadiyah Jember about determining the feasibility of a business using the NVP and IRR methods so that if after graduation they want to build a business, they will already have the provision to determine the feasibility of the business they will build.Keywords: Community service by students, NVP, IRR, Socialization, Financial stewardship analysis